AR-NAVIS: Mobility Application for Blind and Deaf Students Based on Augmented Reality - Joko Slamet Saputro; Gunardi Gunardi; Fadjri Kirana Anggarani; Najya Anastasya; Reva Setiabudi; Sutrisno Ibrahim (Journal of Electrical, Electronic, Information, and Communication Technology, 2024)
Students with disabilities, especially those with visual and hearing impairments, face challenges in navigating through the campus environment. Hence, the development of AR-NAVIS as an Augmented Reality (AR)-based mobility orientation application stands as a significant innovation in providing services for them. This application aims to assist disabled students in moving within the campus environment, both indoors and outdoors. AR-NAVIS identifies the safest and most efficient routes, enabling disabled students to engage in independent activities and enhancing both their academic and non-academic performance. The application development process involves analyzing students' needs, prototype design, model validation, trials, and dissemination. Its features include AR-based 3D guidance, directional text, voice, vibration mode, and hazard information. The app is expected to provide accurate information about buildings or locations that are the destination for disabilities students. The result show that application development can guide disabilities user move between buildings smoothly. The experiment found that there was an increase in student activity after having this application.